Study of Biokinetic Properties and Optimization of the Conditions of Propagation of Recombinant Asporogenic Strain Producing Anthrax Agent Protective Antigen - S. A. Eremin; N. I. Mikshis; O. A. Volokh; O. M. Kudryavtseva; I. A. Shepelev; A. Yu. Goncharova; Yu. A. Popov; A. K. Nikiforov (Проблемы особо опасных инфекций, 2010)
Recombinant Bacillus anthracis strain 55∆ ТПА-1Spo- passed in vitro preserved its asporogenic property and ability to replicate recombinant plasmid. Synthesis of immunogenic protein by genetically engineered producer did not depend on CO2 content in the atmosphere. Determined were the conditions of propagation of asporogenic strain to increase the production of protective antigen. Using Bacillus anthracis asporogenic strain in technological process will provide the safe and ecological procedure of obtaining the major component of chemical anthrax vaccine.